2020
DOI: 10.1155/2020/8580451
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Four Molecular Methods for Detection of Aflatoxin-Producing Aspergillus in Peanut and Dried Shrimp Samples Collected from Local Markets around Pathum Thani Province, Thailand

Abstract: Aspergillus flavus is an aflatoxin-producing fungus which is poisonous to humans and animals when consumed. Detecting the fungus can help to prevent this danger. The four molecular methods, namely, conventional isothermal amplification (LAMP), PCR, quantitative LAMP (qLAMP), and qPCR, were compared to determine their efficiency for A. flavus detection. Thirty samples of peanut and dried shrimp were collected from 15 markets around Pathum Thani Province in Thailand. The samples were artificially infected with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…While outside the laboratory on day 45, none of the LAMP product was observed on all surfaces. However, when all DNA samples buried outside the laboratory were analyzed using qLAMP, the LAMP product was detected which agrees with the work of Kumsiri and Kanchanaphum [ 7 ] and Vichaibun and Kanchanaphum [ 8 ]. Their results indicated that the efficiency and sensitivity of qLAMP were better than those of conventional LAMP.…”
Section: Discussionsupporting
confidence: 88%
“…While outside the laboratory on day 45, none of the LAMP product was observed on all surfaces. However, when all DNA samples buried outside the laboratory were analyzed using qLAMP, the LAMP product was detected which agrees with the work of Kumsiri and Kanchanaphum [ 7 ] and Vichaibun and Kanchanaphum [ 8 ]. Their results indicated that the efficiency and sensitivity of qLAMP were better than those of conventional LAMP.…”
Section: Discussionsupporting
confidence: 88%
“…These differences between molecular and culture-based methods have been observed previously where the low growth speed of fungal species was pinpointed as the main reason for the lack of their detection in culture systems, on the one hand, and high spore prevalent fungi as being on the basis of preferential detection by molecular-based methods, on the other hand [ 51 ]. Importantly, qPCR allows the detection of toxigenic species which are not possible to distinguish microscopically [ 52 ]. The presence of the Aspergillus sections Nidulantes and Circumdati also identified by molecular biology tools, reveals an important contamination by potential toxigenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…These methods can provide rapid screening for aflatoxin-producing moulds in food and feed samples. For the conventional PCR and multiplex PCRbased detection, different housekeeping genes coding for ribosomal RNA and or genes, viz., aflM, aflP, aflR, and aflOinvolved in the aflatoxins biosynthesis (Adetunji et al, 2019) can be amplified to detect the contamination of Aspergillus flavus in food grains Mangal et al, 2016); whereas for the quantitative estimation using real-time PCR (qPCR) the Aspergillus norsolorinic acid reductase gene (NOR1) can be selected (Sardiñas et al, 2011;Kumsiri and Kanchanaphum, 2020). Similarly, LAMP-based strategy was developed to amplify the Norsolorinic Acid gene (nor1) to distinguish aflatoxigenic and non-aflatoxigenic fungal strains in rice grain (Douksouna et al, 2020).…”
Section: Molecular Techniquesmentioning
confidence: 99%